1991
DOI: 10.1111/j.1745-3984.1991.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Procedures for Computing IRT Equating Coefficients

Abstract: In order to equate tests under Item Response Theory (IRT), one must obtain the slope and intercept coefficients of the appropriate linear transformation. This article compares two methods for computing such equating coefficients–Loyd and Hoover (1980) and Stocking and Lord (1983). The former is based upon summary statistics of the test calibrations; the latter is based upon matching test characteristic curves by minimizing a quadratic loss function. Three types of equating situations: horizontal, vertical, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 11 publications
7
52
0
Order By: Relevance
“…Again, item difficulty parameters tend to yield more stable estimates than item discrimination parameters (the mean/sigma method uses only item difficulty parameters), but sample means tend to yield more stable estimates than sample standard deviations (Baker & Al-Karni, 1991).…”
Section: Mean/sigma Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Again, item difficulty parameters tend to yield more stable estimates than item discrimination parameters (the mean/sigma method uses only item difficulty parameters), but sample means tend to yield more stable estimates than sample standard deviations (Baker & Al-Karni, 1991).…”
Section: Mean/sigma Methodsmentioning
confidence: 98%
“…An advantage of the mean/mean method (over the mean/sigma method) is that the sample mean tends to yield more stable estimates of the respective population value than the sample standard deviation (Baker & Al-Karni, 1991). However, item difficulty parameters tend to yield more stable estimates than item discrimination parameters (Kolen & Brennan, 2004).…”
Section: Mean/mean Methodsmentioning
confidence: 99%
“…Another approach for calculating the linking coefficients are characteristic curve methods. These methods are based on minimizing a loss function that depends on the metric of test calibration (Baker & Al-Karni, 1991). Characteristic curve methods consider all parameters simultaneously to find linking coefficients that minimize differences in the characteristic curve between tests.…”
Section: Irt Test Equatingmentioning
confidence: 99%
“…It is known that characteristic curve scale linking methods produce more accurate results than the moment methods (Baker & Al-Karni, 1991;Hanson & Beguin, 2002;Kim & Cohen, 1992;Kim & Kolen, 2006;Kim & Lee, 2004;Ogasawara, 2001). Could we generalize this evident to mixed-format test equating?…”
Section: The Purpose and Significance Of The Studymentioning
confidence: 99%
“…Mean-mean and mean-sigma methods are based on the transformation of item and ability parameters using common items, whereas characteristic curve methods are based on reducing the gap between the item or test characteristic curves of common items. Research has revealed that characteristic curve methods are better than meanmean and mean-sigma methods and tend to produce more stable results (Baker & Al-Karni, 1991;Gök, 2012;Stocking & Lord, 1983).…”
Section: Separate Calibration Irm-scmentioning
confidence: 99%